Effects of a video game intervention on symptoms, training motivation, and visuo-spatial memory in depression - Bergmann, Moritz; Wollbrandt, Ines; Gittel, Lisa; Halbe, Eva; Mackert, Sarah; Philipsen, Alexandra; Lux, Silke (Frontiers in Psychiatry, 2023)
Background People with Major Depressive Disorder (MDD) often experience reduced affect, mood, and cognitive impairments such as memory problems. Although there are various treatments for MDD, many of them do not address the cognitive deficits associated with the disorder. Playing 3D video games has been found to improve cognitive functioning in healthy people, but it is not clear how they may affect depressed mood and motivation in people with MDD. The aim of this study was to investigate whether a six-week video game intervention leads to improvements in depressed mood, training motivation, and visuo-spatial (working) memory functions in patients with MDD. Methods A total of 46 clinically depressed individuals were randomly assigned to one of three groups: an experimental “3D video gaming” group (n = 14) which played a video game, an active control group (n = 16) which trained with a computer program “CogPack,” and a treatment-as-usual group (n = 16) which received a standard clinical treatment including psychotherapy and/or pharmacotherapy. Participants performed a neuropsychological assessment, including self-report questionnaires asking for depressive symptoms, training motivation, and visuo-spatial (working) memory functions before and after the training intervention. Results Regarding depressive symptoms, a significant decrease in the proportion of participants who showed clinical levels of depressive symptoms as measured by the Beck Depression Inventory was only found in the 3D video gaming group. Additionally, mean motivational levels of performing the training were significantly higher in the 3D video gaming group when compared with the active control group. Moreover, whereas the 3D Video Gaming group only significantly improved on one visuo-spatial memory test, the active control group improved in all visuo-spatial memory functions. The 3D video gaming group did not perform significantly better than the CogPack group, and the TAU group. Conclusion Besides a standalone cognitive training, the current findings suggest that cognitive trainings using a video game have potential to increase subjective well-being, show higher levels of training motivation, and lead to improvements in visuo-spatial (working) memory functions in MDD. However, given the mixed and unblinded nature of this study, the results should be interpreted with caution. Further research with larger samples and follow-up measurements is needed.